Didactic sequence of software to work the content living beings with students from the initial years of Elementary School (Research, Society and Development, 2019)
Technology is permeating the lives of people daily, becoming present in the different spaces that we inhabit. In the classroom it can serve the teachers' practices and be a powerful ally when it comes to improving various contents. This article aims to subsidize initial years teachers of Elementary Education to develop pedagogical situations with the use of educational software with their students, bringing digital technology closer to the classroom. For that, a didactic sequence was elaborated, which in its entirety can be considered an educational product, containing pedagogical proposals for the development of living beings contents in the initial years, through the use of five free access software. The material developed comes from the activities of students of postgraduate courses (masters and doctorates) of a community institution in the municipality of Lajeado, State of Rio Grande do Sul. The first software (Mentimeter) was explored with the graduate students, through pilot testing in the classroom and subsequent collection of reports via WhatsApp. It was verified that the participants considered the experience valid and believe that it is potent to be developed with the students of the initial years of Elementary School, allowing greater involvement and the promotion of more dynamic and participative classes.